(Cyber)Bullying in schools: when bullying stretches across cON/FFlating spaces - Bork-Hüffer, Tabea; Mahlknecht, Belinda; Kaufmann, Katja (Children's geographies, 2021)
This article posits that analyses of (cyber)bullying among digitally connected young people need to explore the interdependences, intersections and cON/FFlation of bullying in ONline and OFFline spaces. It combines digital geographers’ works on relationalities between digital and offline spaces with studies on children’s and young people’s geographies and digitization as well as with interdisciplinary work on cyberbullying and traditional bullying in the school context. Drawing on narratives written by young people in Austria, the article lets participants speak through their own voices. There is an urgent need for disparate research examining either or both traditional and cyberbullying, to take note not only of each of their inimitable spatialities, but also their intersections. Through taking a perspective of cON/FFlating spaces we seek to produce a better understanding of the cON/FFlating nature and spaces of bullying in the digital era and to deepen the conceptualization of these interlinked and entangled socio-material-technological spaces.
Gesehen am 16.04.2025
Online veröffentlicht: 28. Juni 2020